PERAN KELEMBAGAAN DALAM PENGEMBANGAN AGRIBISNIS MENDONG - Tenten Tedjaningsih; Suyudi Suyudi; Hendar Nuryaman (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
The success of farming implemented will not be separated from institutional role of agribusiness. If the role is not yet optimal then commodity agribusiness development will be hampered. This study aims to determine the satisfaction of farmers on the institutional performance of agribusiness mendong. The research was conducted by using survey method in Manonjaya Sub district, Tasikmalaya Regency. The sample used is 25 farmers mendong, sampling using simple random sampling. To know the institutional performance of agribusiness used Importance Performance Analysis (IPA), while to see farmer satisfaction on institutional performance use Consumer Satisfaction Index (CSI). The result of the research shows that for the agribusiness institution performance, the farmers are satisfied with the kiosks of production facilities, collectors / dealers, artisans, farmers, extensionists and universities that perform well in performing the institutional function of agribusiness in Mendong farming. Priority to improve the institutional function lies in the existence of cooperatives, purchase requirements mendong, selling prices mendong, farmers group as a production unit and provider of production facilities and training by information and technology institutions. As for institutional performance shows that institutional agribusiness mendong still need to be improved again in order to be able to face challenge of competition with strengthening of farmer independence through improvement of function farmers group as production unit and procurement of production means so that there is increase of added value and exchange rate from its farming activity by not apart from training application of technological innovation from related institutions.Keywords: Institutional, Agribusiness, Interest, Performance, Satisfaction